Analisis XRD dan Leaching Out dari Solidifikasi/Stabilisasi Ion Logam Cr(VI) Menggunakan Semen - Shinta Bella; Jon Efendi (Jurnal Periodic Jurusan Kimia UNP, 2021)
Cr (VI) metal waste becomes one of the heavy metal wastes which is very difficult to overcome. For this reason, the Cr (VI) waste processor uses a stabilization / solidification method to reduce the concentration of Cr (VI) metal ions in the environment by using cement as a binder. The testing setting time for cement is that by increasing the Cr (VI) concentration, the longer it takes for the cement hardening process. This is in line with the results of the compressive strength test, where the results for concentrations of 0.5%, 2%, and 5% were 32, 26, and 23 MPa, respectively. whereas according to the US EPA, the minimum compressive strength test is 0.3 MPa. TCLP test for 96 hours for this method is that the higher the concentration, the higher the Cr (VI) leaching in cement.